Circadian Rhythm in Adipose Tissue: Novel Antioxidant Target for Metabolic and Cardiovascular Diseases - Andy W. C. Man; Ning Xia; Huige Li (MDPI AG, 2020)
Obesity is a major risk factor for most metabolic and cardiovascular disorders. Adipose tissue is an important endocrine organ that modulates metabolic and cardiovascular health by secreting signaling molecules. Oxidative stress is a common mechanism associated with metabolic and cardiovascular complications including obesity, type 2 diabetes, and hypertension. Oxidative stress can cause adipose tissue dysfunction. Accumulating data from both humans and experimental animal models suggest that adipose tissue function and oxidative stress have an innate connection with the intrinsic biological clock. Circadian clock orchestrates biological processes in adjusting to daily environmental changes according to internal or external cues. Recent studies have identified the genes and molecular pathways exhibiting circadian expression patterns in adipose tissue. Disruption of the circadian rhythmicity has been suggested to augment oxidative stress and aberrate adipose tissue function and metabolism. Therefore, circadian machinery in the adipose tissue may be a novel therapeutic target for the prevention and treatment of metabolic and cardiovascular diseases. In this review, we summarize recent findings on circadian rhythm and oxidative stress in adipose tissue, dissect the key components that play a role in regulating the clock rhythm, oxidative stress and adipose tissue function, and discuss the potential use of antioxidant treatment on metabolic and cardiovascular diseases by targeting the adipose clock.